PENGGUNAAN “GREEN COSMETIC” DALAM MEWUJUDKAN PERILAKU KESADARAN LINGKUNGAN - Ingrid Weddy; Viva Febrya (Jurnal Ilmu Lingkungan, 2016)
The purpose of this study are, (1). To analyze the knowledge of consumers about environmentally friendly cosmetics, (2). To analyze the characteristics of environmentally friendly consumer cosmetics users. The type of research used descriptive analytical. Processing and data analysis use qualitatively method. The data analysis done by describing and interpreting the data obtained. Population and sample consumer research is the Body Shop member, as many as 30 people were selected by random sampling. Methods of data collection in this research through: (a) the knowledge test is used for consumer knowledge about environmentally friendly cosmetics, (b) A questionnaire was used to determine the characteristics of consumers. The results of the study are : (1) There is still a lack of knowledge of consumers towards environmentally friendly cosmetics, (2) Consumers tend to buy products based on price is cheap.